Inefficient water pricing and incentives for conservation - Ujjayant Chakravorty; Manzoor H. Dar; Kyle Emerick (Center for Economic Studies and ifo Institute (CESifo), 2019)
We use two randomized controlled trials in Bangladesh to study a simple water conservation technology for rice production called “Alternate Wetting and Drying (AWD)”. Despite proven results in agronomic trials, our first experiment shows that AWD only saves water and increases profits in villages where farmers pay a marginal price for water, but not when they pay fixed seasonal charges. The second RCT randomly distributed debit cards that can be used to pay volumetric prices for irrigation water. This low-cost, scalable intervention causes farmers to place more value on the water-saving technology. Demand for the technology becomes less price-sensitive.
Keywords: 330